Freshwater ascomycetes from north Maharashtra-IV - Patil, S Y; Borse, B D (Current Botany, 2012)
The present paper deals with two species of Aniptodera Shearer & Miller the freshwater ascomycetes viz. Aniptodera chesapeakensis Shearer & Miller and Aniptodera lignicola Hyde, Ho & Tsui were collected from the submerged wood samples from the various water bodies in North Maharashtra region. Aniptodera lignicola Hyde, Ho & Tsui is being recorded for the first time form India, while Aniptodera chesapeakensis Shearer & Miller is being reported for the first time from freshwater habitat from India. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.